Impact of Chronic Medical Conditions on Academics of Children in the Child Welfare System - Whitgob, Emily E.; Loe, Irene Marilyn (Frontiers in Public Health, 2018)
Objective: Children in the Child Welfare System (CWS) are at high risk for multiple adverse outcomes. Since involvement in CWS and having a chronic medical condition are both risk factors for poor academic achievement, a logical view is that the combination is additive, increasing the odds of poor performance. However, several factors may complicate such an association. This study explores negative and positive factors that could affect academic achievement in children in CWS with chronic medical conditions. Method: In a secondary data analysis of a nationally representative, longitudinal sample of children in CWS(N=5501), subjects were divided into 3 groups based on chronic medical condition: High Prevalence, Low Severity (HPLS; asthma, eczema, allergy, diabetes), Other (OTH; all other chronic conditions, including those with primary central nervous system involvement), and NONE (children with no chronic condition). Using weighted analyses, hierarchical logistic regression models addressed factors associated with academic achievement. Predictor variables included chronic condition group, sex, income level, case substantiation, home placement, and school engagement. Intelligence quotient was a covariate. Outcome variables were strong performances for reading and math, defined by standard score ≥85. Results: In TOTAL group, 80% had strong reading; more in HPLS (85%) vs NONE (79%) and OTH (80%), adjusted F=433, p<.001. In TOTAL group, 67% had strong math; more in NONE (68%) and HPLS (68%) vs OTH (60%), adjusted F=1278, p<.001. Models predicting to strong reading and math achievement were significant, R2=.51, p<.001 and R2=.43, p<.001, respectively. HPLS had increased odds of strong reading achievement (aOR 1.3, 95% CI 1.3-1.4); both HPLS and OTH had lower odds of strong math achievement (aOR .87 and .76), p<.001, respectively. Male sex and negative school engagement had lower odds of strong reading (aOR 0.44 and 0.85) and math achievement (OR 0.62 and 0.49), all p< .001. Conclusion: If true, our findings challenge the general belief that chronic illness can only be associated with negative outcomes and that cumulative adversities are simply additive in terms of risk. Increased contact with the medical system may provide an opportunity for improving reading achievement for children in CWS and promoting positive school engagement.